Life insurance in Islamic law : a comparative study between Syarikat Takaful Malaysia Bhd and Takaful Ikhlas Sdn Bhd Malaysia - Shalim, K. M. Zakir Hossain (Kulliyyah of Islamic Revealed Knowedge and Human Sciences, International Islamic University Malaysia, 2010)
Life insurance is an important financial tool through which the individuals can obtain financial security for their families and businesses. Muslim jurists have different views on it. Some have maintained that it is permissible in Islam, while some others have rejected it. This study attempts to discuss and examine the different views of the Muslim jurists on this issue. In addition, in order to see application of Shariah principles in existing Islamic life insurance companies, this study makes a comparative study between two leading takaful operators in Malaysia. These are: Syarikat Takaful Malaysia Bhd (STMB) and Takaful Ikhlas Sdn Bhd (TISB).This study used two methods of data collection: library research and consultation with experts in Islamic insurance (takaful) as well as interviews with the staff of STMB and TISB. This study has reached to a number of findings. Most important among them are: this research proves that life insurance is permissible in Islam, if some measures are taken to avoid some unlawful elements in it; both STMB and TISB are silent on the legal right of receiving takaful benefits for a beneficiary who becomes a non-Muslim or apostate. Muslim scholars have criticized both STMB and TISB in this regard; both STMB and TISB apply the principle of tabarru' in their takaful operations. After analyzing the scholars arguments on the proper applicability of the principle of tabarru' in takaful operations, this study maintains that the concept of the tabarru' in both STMB and TISB should be reviewed. Additionally, this study finds that though the practices of Islamic life insurance in both STMB and TISB have rendered most of the Shariah conditions, there are some issues which still need to be reviewed by the both STMB and TISB. In order for this review, this research suggests that STMB should repay the surplus to the policyholders; on the other hand, TISB should not take the responsibility of managing surplus or decision maker. This is because the policyholders are the main owners of the surplus. They are ones who should decide how surplus should be distributed. Moreover, this research also suggests that the balance shown in PSA as tabarru' should not be regarded as tabarru' for STMB and TISB; rather, it should be regarded tabarru' for participants of these companies because it is considered one type of gharar.